(untitled) (Community Based Medical Journal, 2026)
Anal fistulas pose significant therapeutic challenges, particularly high trans-sphincteric variants where recurrence and incontinence risks complicate management. Conventional seton techniques, while effective, often require multiple adjustments. The rubber band seton offers potential advantages through gradual, controlled cutting action, potentially reducing morbidity while maintaining therapeutic efficacy, warranting detailed clinical evaluation. A cross-sectional, descriptive study was conducted in the Department of Surgery, Bangabandhu Sheikh Mujib Medical University (BSMMU), Dhaka, Bangladesh, from October 2012 to March 2013, to assess the outcomes of rubber band seton in the treatment of anal fistula. A total of 50 patients with high trans-sphincteric anal fistulas were included in this study. The rubber band seton was inserted through the fistula tract as a single strand and secured with 4-5 tight knots. Patient demographics, clinical presentation, treatment outcomes, and postoperative complications were systematically recorded. Among 50 patients, the median age was 40 years; 82% were males. High trans-sphincteric fistulas were observed (30% anterior, 70% posterior). Postoperative complications were minimal (4% urinary retention), with all patients discharged within 24 hours without narcotics. Cutting time was 1-3 months, with 10% experiencing premature loosening that healed spontaneously. Complete healing rates reached 46% at 1 month and 100% by 3 months, with 4% recurrence and 16% developing transient mild incontinence. Preliminary results suggest rubber band setons effectively treat high anal fistulas while preserving continence through gradual sphincter cutting. This method eliminates postoperative adjustments required with conventional setons, offering a promising alternative. CBMJ 2026 January: vol. 15 no. 01 P:211-215